Global regulatory issues for the cosmetics industry. Volume 1 - Betton, C. I. (W. Andrew Pub., 2007)
The manufacture and use of cosmetics is an international undertaking unparalleled by any other industry. Regulation of this industry, however, is neither universal nor consistent. The purpose of this book (the first of a series) is to simplify the complex global Cosmetic Regulatory landscape by addressing the issues affecting the manufacture, packaging, and marketing of cosmetic products across the globe. Included are several chapters that examine the new European Union REACH regulation (Registration Evaluation and Authorization of CHemicals). Other chapters look at regulatory developments of individual countries, toxicity requirements, as well as how to develop a global regulatory strategy.
Keywords: Cosmetics -- Law and legislation.; Cosmetics industry.; elektronické knihy; electronic books